Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Keaktifan dan Motivasi Belajar Siswa Mata Pelajaran Simulasi dan Komunikasi Digital Siswa Kelas X SMK Negeri 2 Baubau Tahun Pelajaran 2018/2019 - Ela Nurmala (Jurnal Akademik FKIP Unidayan, 2019)
The objective of this research was to find out students’ learning activeness and students’ learning motivation through the application of project based learning model at students of SMKN 2 Baubau. This was a classroom action research conducting at class X1 building technique SMKN 2 Baubau in school year 2018/2019. This research was conducting on 2 cycles. The data of this research was collected from observation and questionnaire. After the data were collected, then they were analyzed by using a quantitative descriptive analysis. The result showed that, the application of Project based learning model can increase students’ learning activeness, and students learning motivation at class X1 building technique department at SMKN 2 Baubau.